2022
DOI: 10.1186/s12894-022-01109-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hemodynamic instability during laparoscopic resection of pheochromocytoma

Abstract: Background Laparoscopic adrenalectomy for pheochromocytoma is associated with high risk of intraoperative hemodynamic instability. Our study aimed to identify predictive factors for hemodynamic instability during laparoscopic resection of pheochromocytoma. Methods Between January 2011 and December 2021, 136 patients underwent unilateral laparoscopic adrenalectomy for pheochromocytoma. The patients were divided into 2 groups depending on the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In agreement with our results, recently, one study in 136 patients who underwent unilateral laparoscopic adrenalectomy for pheochromocytoma showed that previous hypertension history was an independent risk factor for intraoperative hemodynamic instability. In this study, patients with hemodynamic instability had greater BP fluctuations and higher maximum BP during surgery [28]. Although the characteristics of normotensive PPGL are poorly known, it seems that normotensive patients have smaller tumors and lower secretion of catecholamines.…”
Section: Discussionmentioning
confidence: 54%
“…In agreement with our results, recently, one study in 136 patients who underwent unilateral laparoscopic adrenalectomy for pheochromocytoma showed that previous hypertension history was an independent risk factor for intraoperative hemodynamic instability. In this study, patients with hemodynamic instability had greater BP fluctuations and higher maximum BP during surgery [28]. Although the characteristics of normotensive PPGL are poorly known, it seems that normotensive patients have smaller tumors and lower secretion of catecholamines.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, we observed 399(66.72%) patients had HT history at admission. Carefully monitoring of blood pressure before operation and HT history had already been raised awareness because these might be risk factors of hemodynamic instability during the removal of pheochromocytoma [11]. Although previous studies investigated LVMI in PPGL, the majority of them compared PPGL and EH patients, indicating that LVH was a prominent cardiac performance in PPGL than EH [4,12].…”
Section: Discussionmentioning
confidence: 99%